2016
DOI: 10.1155/2016/3285074
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Hydrogen Sulfide in Glucose Regulation: How H2S Can Alter Glucose Homeostasis through Metabolic Hormones

Abstract: Diabetes and its comorbidities continue to be a major health problem worldwide. Understanding the precise mechanisms that control glucose homeostasis and their dysregulation during diabetes are a major research focus. Hydrogen sulfide (H2S) has emerged as an important regulator of glucose homeostasis. This is achieved through its production and action in several metabolic and hormone producing organs including the pancreas, liver, and adipose. Of importance, H2S production and signaling in these tissues are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 43 publications
0
38
0
2
Order By: Relevance
“…The Sox system appears to be advantageous in this point because its target is H 2 S produced by oral bacteria, not oral bacteria or oral tissues. Furthermore, previous studies reported that H 2 S participates in physiological regulation in the human body (28, 46, 50). Therefore, the Sox system has potential as an effective agent for controlling body systems as a H 2 S regulator.…”
Section: Discussionmentioning
confidence: 96%
“…The Sox system appears to be advantageous in this point because its target is H 2 S produced by oral bacteria, not oral bacteria or oral tissues. Furthermore, previous studies reported that H 2 S participates in physiological regulation in the human body (28, 46, 50). Therefore, the Sox system has potential as an effective agent for controlling body systems as a H 2 S regulator.…”
Section: Discussionmentioning
confidence: 96%
“…Hayden et al ( 59 ) have also shown elevated blood glucose levels after exposure with H 2 S. Pichette and Gagnon summarize the literature on the effects of H 2 S and glucose regulation, indicating that mechanisms besides insulin regulation, such as glucagon-like-peptide (GLP)-1 or peptide YY are involved ( 60 ). Our data confirm findings of Lin et al ( 61 ) that exogenous H 2 S protects cells by its glucose reducing activity.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM), either type-1 diabetes mellitus (T1DM) or type-2 diabetes mellitus (T2DM), is a lifelong condition that affects millions of individuals worldwide [ 1 , 2 ], and it represents a strong risk factor for the development of atherosclerotic coronary and peripheral arterial disease [ 3 , 4 ]. It has been reported that changes in the balance of hydrogen sulfide (H 2 S) play an important role in the pathogenesis of β-cell dysfunction that occurs in response to T1DM and T2DM [ 5 , 6 ]. H 2 S is synthesized by mammalian tissues, and it serves various important regulatory functions [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%